Reorientasi Keterampilan Teknis Supervisi Akademik Dalam Kolaborasi Profesional Guru Di Lembaga Pendidikan Islam - Ajril Akmal; Yonanda Kumala Nasrilia; Indah Aminatuz Zuhriyah; Baharuddin Baharuddin (Najah Bestari, 2026)
The research employed a qualitative approach using a literature review design through systematic searches and analyses of journal articles, books, and other scientific publications related to academic supervision and teacher professional development. Data were analyzed using thematic analysis to identify recurring patterns, key concepts, and gaps between conceptual expectations and actual supervision practices. The findings reveal that observation skills are fundamental to academic supervision, yet they are often conducted merely for administrative purposes. Assessment and planning processes are not fully data-driven or collaborative, while implementation and evaluation tend to be unsustainable and rarely followed by meaningful actions. This study contributes conceptually by strengthening the framework of technical supervision skills grounded in teacher professional collaboration. It concludes that supervisors’ technical competencies must be enhanced so that academic supervision moves beyond procedural routines and becomes a driver of real improvements in teaching practices. The study also offers theoretical implications for Islamic educational supervision and practical guidance for principals and supervisors in designing more effective, collaborative, and sustainable supervision systems.